John Hughlings Jackson and our understanding of the epilepsies 100 years on. Issue 1 (14th January 2011) - Iniesta, Ivan
Abstract : The term Jacksonian epilepsy was coined by Jean Martin Charcot following John Hughlings Jackson's 1870 paper 'A study of convulsions', where he had defined a convulsion as "a symptom resulting from an occasional, an excessive and a disorderly discharge of nerve tissue on muscles". His earlier writings had included cases of syphilis related epilepsy, and the introduction of the first successful antiepileptic drugs—the bromides. Based on careful clinical observation or, as Hughlings Jackson himself put it, on the "experiments performed by disease", 'A study of convulsions' was a synthesis of those previous reports which has contributed to our practical understanding of epilepsy, a contribution which continues to inform our thinking to the present day.